Faktor-faktor yang mempengaruhi kemampuan kognitif pada lansia obesitas di Indonesia - Yoseph Leonardo Samodra; Neni Trilusiana Rahmawati; Sumarni Sumarni (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2018)
Background: Elderly (>60 years old) population is growing in Indonesia. It is important to prevent degradation of cognitive capacity by risk factor identification and treatment.Objective: To identify the relationship between anthropometric status and cognitive capacity on elderly population.Method: This is an analysis of The Fifth Wave of the Indonesia Family Life Survey (IFLS5) data with cross-sectional design. Anthropometric status is consisted of: body weight, body height, body mass index (BMI), knee height, upper arm length, waist circumference, hip circumference, and waist-hip ratio (WHR). Cognitive capacity is measured by modified telephone survey of cognitive status (TICS). Chi-Square and Mann-Whitney test are used for bivariate analysis, logistic regression is used for multivariate analysis.Results: Variables with significant relationship to cognitive capacity are body weight (p=0.0002), body height (p=0.0001), knee height (p=0.0387), upper arm length (p=0.0114), age (p=0.011), sex (p=0.014), and history of hypercholesterolemia (p=0.003). Logistic regression shows that body height, age, and history of hypercholesterolemia are simultaneously affecting cognitive capacity.Conclusion: There is significant relationship between body height, body weight, upper arm length, knee height, and cognitive capacity on elderly population with obesity.